Sericin/crocetin micro/nanoparticles for nucleus pulposus cells regeneration: An “active” drug delivery system - Bari, Elia; Perteghella, Sara; Rassu, Giovanna; Gavini, Elisabetta; Petretto, Giacomo Luigi; Bonferoni, Maria Cristina; Giunchedi, Paolo; Torre, Maria Luisa (Frontiers in Pharmacology, 2023)
Initiation and progression of intervertebral disk degeneration are linked to oxidative stress, with reactive oxygen species being a key factor. Therefore, as a potentially novel approach able to regenerate the damaged intervertebral disk, this work aimed to prepare an “active per sé” drug delivery system by combining sericin and crocetin: both are bioactive compounds with antioxidant, anti-inflammatory, immunomodulant and regenerative properties. In detail, sericin nanoparticles were prepared using crocetin as a cross-linker; then, the nanoparticle dispersions were dried by spray drying as it is (NP), with an excess of sericin (NPS) or crocin/crocetin (NPMix), obtaining three microparticle formulations. Before drying, the nanoparticles were nanometric (about 250 nm), with a negative surface charge, and appeared spherical and smooth. Following the drying process, spherical and smooth microparticles were obtained, with a mean diameter of about 1.7-2.30 µm. NPmix was the most active in antioxidant and anti-tyrosinase activities, likely due to the excess of crocin/crocetin, while NPS had the best anti-elastase activity, likely due to sericin in excess. Furthermore, all the formulations could prevent oxidative stress damage on nucleus pulposus cells, with NPmix being the best. Overall, the intrinsic anti-tyrosinase and anti-elastase activities and the ability to protect from oxidative stress-induced damages justify future investigations of these “active per sé” formulations in treating or preventing intervertebral disk degeneration.